Rare Earth Borohydrides - Crystal Structures and Thermal Properties - Frommen, C.; Sorby, M.; Heere, M.; Humphries, Terry; Olsen, J.; Hauback, B. (M D P I AG, 2017)
Rare earth (RE) borohydrides have received considerable attention during the past ten years as possible hydrogen storage materials due to their relatively high gravimetric hydrogen density. This review illustrates the rich chemistry, structural diversity and thermal properties of borohydrides containing RE elements. In addition, it highlights the decomposition and rehydrogenation properties of composites containing RE-borohydrides, light-weight metal borohydrides such as LiBH4 and additives such as LiH.